Inconsistency between records of δ18O and trace element ratios from stalagmites : evidence for increasing mid–late Holocene moisture in arid central Asia - Liu, Xiaokang (2020)
The interpretation of trace element/calcium ratios of speleothems as indicators of local hydroclimatic variability in the vicinity of caves has led to controversy in reconstructing the evolution of moisture conditions in arid central Asia (ACA) during the Holocene. Here we present records of Mg/Ca, Sr/Ca, Ba/Ca, and U/Ca from precisely dated stalagmites from Baluk cave in Xinjiang (northwest China), spanning the past 9370 years. The co-variations of the trace element ratios, together with the slopes of the regression lines of the corresponding logarithmically transformed data, suggest that they are dominated by prior calcite precipitation (PCP) and thus can be used as reliable proxies of changes in moisture/precipitation. The trace element ratios are relatively high during ~9 to 5 ka and lower from 5 ka to the present, indicating a trend of increasing mid–late Holocene moisture in ACA. The long-term trend of variation of the trace element ratios is correlative with two other records of speleothem trace element ratios from caves in ACA: Kesang cave (western Xinjiang) and Ton cave (Uzbekistan). This spatial coherency of the trend of inferred moisture conditions from three caves that are separated by hundreds of kilometers demonstrates that speleothem trace element ratios are indicative of large spatial scale rather than local hydroclimatic variability in ACA during the Holocene. However, the long-term trend of variation of the trace element ratios is the inverse of the corresponding oxygen isotope (δ18O) records from the same cave sites, which implies that Holocene speleothem δ18O records do not represent changes in the precipitation amount in ACA; rather, they most likely reflect moisture sources and related water vapor transport controlled by Northern Hemisphere summer insolation (NHSI). Our findings provide new evidence for a ‘westerlies-dominated climatic regime’, which influenced hydroclimatic changes in ACA during the Holocene.